LncRNA XIST promotes adjuvant-induced arthritis by increasing the expression of YY1 via miR-34a-5p - Yazhi Wei,; Liping Dai,; Yanqun Deng,; Zhizhong Ye, (Archives of Rheumatology, 2023)
Objectives: This study aims to explore the mechanism by which long non-coding ribonucleic acids (lncRNA) X-inactive specific transcript (XIST) affects the progression of adjuvant-induced arthritis (AIA). Materials and methods: Freund's complete adjuvant was used to induce arthritis in rats. The polyarthritis, spleen and thymus indexes were calculated to evaluate AIA. Hematoxylin-eosin (H&E) staining was used to reveal the pathological changes in the synovium of AIA rats. Enzyme-linked immunosorbent assay (ELISA) was performed to detect the expression of tumor necrosis factor-alpha (TNF-α), interleukin (IL)-6 and IL-8 in the synovial fluid of AIA rats. The cell continuing kit (CCK)-8, flow cytometry, and Transwell assays were used to assess the proliferation, apoptosis, migration and invasion of transfected fibroblast-like synoviocytes (FLS) isolated from AIA rats (AIA-FLS). Dual-luciferase reporter assay was performed to verify the binding sites between XIST and miR-34b-5p or between YY1 mRNA and miR-34b-5p. Results: The XIST and YY1 were highly expressed, and miR-34a-5p was lowly expressed in the synovium of AIA rats and in AIA-FLS. Silencing of XIST impaired the function of AIA-FLS in vitro and inhibited the progression of AIA in vivo. The XIST promoted the expression of YY1 by competitively binding to miR-34a-5p. Inhibition of miR-34a-5p strengthened the function of AIA-FLS by upregulating XIST and YY1. Conclusion: The XIST controls the function of AIA-FLS and may promote the progression of rheumatoid arthritis via the miR-34a-5p/YY1 axis.